Safety and efficacy of endoscopic ultrasound‐guided fine needle aspiration for pancreatic masses: A prospective multicenter study. Issue 1 (19th July 2019) - Yoshinaga, Shigetaka; Itoi, Takao; Yamao, Kenji; Yasuda, Ichiro; Irisawa, Atsushi; Imaoka, Hiroshi; Tsuchiya, Takayoshi; Doi, Shinpei; Yamabe, Akane; Murakami, Yoshitaka; Ishikawa, Hideki; Saito, Yutaka
Abstract : Objectives: Endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA) for solid pancreatic lesions has high diagnostic yield. However, few prospective multicenter studies have been performed. We performed a prospective cohort study to evaluate the efficacy and safety of EUS‐FNA for diagnosis of solid pancreatic lesions. Methods: This prospective cohort study involved five hospitals in Japan. The primary outcome was sensitivity of EUS‐FNA for diagnosing malignant lesions. We also evaluated parameters of diagnostic sufficiency and the safety of EUS‐FNA. Results: In total, 246 patients were enrolled. The absolute values of the parameters evaluated showed no significant differences; however, the percentage changes in the white blood cell counts and C‐reactive protein levels after examination were significantly higher, and the percentage change in hemoglobin concentrations was significantly lower. The minor and major complication rates at the time of puncture, 24 h, 7 days and 28 days were 4.1%, 2.8%, 1.6%, and 0.0%, respectively. The true complication rate was 1.2%. The diagnostic sensitivity, specificity, accuracy, positive predictive value, and negative predictive value were 97.2%, 88.0%, 96.2%, 100%, and 81.4%, respectively. Conclusions: EUS‐FNA for solid pancreatic lesions has high diagnostic yield and is safe, consistent with previously studies.